2020
DOI: 10.1186/s12943-020-1139-3
|View full text |Cite|
|
Sign up to set email alerts
|

CircPTK2 (hsa_circ_0005273) as a novel therapeutic target for metastatic colorectal cancer

Abstract: Background: As a novel class of noncoding RNAs, circRNAs have been recently identified to regulate tumorigenesis and aggressiveness. However, the function of circRNAs in colorectal cancer (CRC) metastasis remains unclear. We aimed to identify circRNAs that are upregulated in CRC tissues from patients and study their function in CRC metastasis. Methods: We compared six pairs of CRC tissues and their matched adjacent non-tumor tissues by using circRNA microarray. We first evaluated the expression of circPTK2 (hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 42 publications
3
129
0
2
Order By: Relevance
“…The result showed that circRNA played signi cant role in occurrence and development of refractory breast cancer. Yang et al veri ed the RNA expression level of circPTK2 in colon cancer and normal colon tissues, and veri ed that the expression content of circPTK2 is related to the clinical stage of colon cancer patients, and in vitro and PDTX models, veri ed that the increase in circPTK2 expression can be Promote the metastasis of colon cancer [19]. The results of Chen et al con rmed that circSnx5 could act as a miR-544 sponge to reduce Suppressors of cytokine signaling 1 (SOCS1) target inhibition and inhibit the nuclear transport of PU.1, and regulate dendritic cell (DC) activation and function [20].…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that circRNA played signi cant role in occurrence and development of refractory breast cancer. Yang et al veri ed the RNA expression level of circPTK2 in colon cancer and normal colon tissues, and veri ed that the expression content of circPTK2 is related to the clinical stage of colon cancer patients, and in vitro and PDTX models, veri ed that the increase in circPTK2 expression can be Promote the metastasis of colon cancer [19]. The results of Chen et al con rmed that circSnx5 could act as a miR-544 sponge to reduce Suppressors of cytokine signaling 1 (SOCS1) target inhibition and inhibit the nuclear transport of PU.1, and regulate dendritic cell (DC) activation and function [20].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, samples were incubated with Hsa_circ_0000826 probes at 40°C for 2 hours. After hybridization, a series of single amplification procedures were performed and finally visualized with Fast Red 11 . The number of puncta was calculated in 200 cells/group.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the expression levels hsa_circ_0124055 and hsa_circ_0101622 in tumour tissues and plasma of patients with thyroid cancer are significantly increased, and the overall survival times of patients with a high expression level of either circRNA were shorter than those of patients with a low expression level of either circRNA. These results suggest that both of these circRNAs are helpful biomarkers for the prognosis and diagnosis of thyroid carcinoma and can be used as clinical therapeutic targets [112]. In addition, regarding drug resistance, hsa_circ_0006528 [113], circMTO1 [114], circ_0001546 [115], and circ-LARP4 [116] exhibit abnormal expression levels in drug-resistant cells, suggesting that they could be used as diagnostic markers for drug resistance in tumours.…”
Section: Potential Of Circrnas As Biomarkersmentioning
confidence: 99%